Library Management in the University of Jammu post COVID-19: A Case Study of Students’ Perspective (LIS TODAY, 2022)
The current study attempts to build an analysis of frame of mind of the students concerning the library  management in the University of Jammu post COVID-19. Management is an activity of planning and  perpetuating suitable conditions to obtain the desired performance and effectiveness in achieving objectives of  the organisation. Management is multifaceted and its stretch is huge as it encompasses resources such as  infrastructure, technology-based resources, manpower and economic resources.
Keywords: Dhanvantri Library; COVID-19; Information; Library; Library Management; University of Jammu